Pengaruh Waktu Hidrotermal terhadap Karakteristik Zeolite Socony Mobile-5 (ZSM-5) Tanpa Template Menggunakan Reaktor Autoclave: The Effect of Hydrotermal Time in Characteristics of Zeolite Socony Mobile-5 (ZSM-5) Without Template Using Autoclave Reactor - Mukhtar Ghozali; Gamaliel Tanaka; Muhammad Misbahussalam; Tifa Paramitha (KOVALEN: Jurnal Riset Kimia, 2021)
ZSM-5 is a synthetic zeolite which has a complex production process and is affected by operating conditions, such as temperature and time. In this study, synthesized ZSM-5 without template by hydrothermal method. An autoclave reactor was used for the hydrothermal process. The aim of this study was to investigate the effect of varied hydrothermal times of 24 and 48 hours with a hydrothermal temperature of 180oC on the characteristic of ZSM-5. The raw materials used were silica oxide and aluminum hydroxide as a source of silica and alumina. The synthesis results were characterized using X-Ray Diffraction (XRD). Based on XRD results, the best result was obtained in performed at 48 hours hydrothermal time indicating the formation of ZSM-5 material at the 22.2o position. The percentage crystallinity of the sample at the hydrothermal time of 48 hours was 51.3%.